Respuesta :
1st condition: x + y + z = 4
2nd condition: y = 2x + 1
3rd condition: x + z = - 1 <=> z = - x - 1
Based on the 2nd and 3rd, we replace the 1st as following:
x + 2x + 1 - x - 1 = 4 <=>
2x = 4 <=>
x = 2
Since x = 2, we solve the 2nd as following:
y = 2x + 1 <=>
y = 2*2 + 1 <=>
y = 4 + 1 <=>
y = 5
Same thing for the 3rd:
z = - x - 1 <=>
z = - 2 - 1 <=>
z = - 3
2nd condition: y = 2x + 1
3rd condition: x + z = - 1 <=> z = - x - 1
Based on the 2nd and 3rd, we replace the 1st as following:
x + 2x + 1 - x - 1 = 4 <=>
2x = 4 <=>
x = 2
Since x = 2, we solve the 2nd as following:
y = 2x + 1 <=>
y = 2*2 + 1 <=>
y = 4 + 1 <=>
y = 5
Same thing for the 3rd:
z = - x - 1 <=>
z = - 2 - 1 <=>
z = - 3
1. The first number is equal to 2.
2. The second number is equal to 5.
3. The third number is equal to -3.
- Let the first number be a.
- Let the second number be b.
- Let the third number be c.
Translating the word sentence into an algebraic expression, we have;
The sum of three numbers is 4:
[tex]a+b+c=4[/tex] ....equation 1.
The second number is 1 more than twice the first:
[tex]b=2a+1[/tex] ....equation 2.
The sum of the first and third is –1:
[tex]a+c=-1[/tex] ....equation 3.
From eqn. 3, we have:
[tex]c=-1-a[/tex] ....equation 4.
Substituting into eqn. 1, we have:
[tex]a+2a+1+(-1-a)=4\\\\3a+ 1-1-a=4\\\\2a=4\\\\a=\frac{4}{2}[/tex]
a = 2
To find the value of b:
[tex]b=2a+1\\\\b=2(2)+1\\\\b=4+1[/tex]
b = 5
To find the value of c:
[tex]c=-1-a\\\\c=-1-2\\\\[/tex]
c = -3
Read more: https://brainly.com/question/16049